Drag reduction characteristics using aloe vera natural mucilage: An experimental study - Abdulbari, Hayder A.; Letchmanan, Kumaran; R. M., Yunus (Asian Network for Scientific Information, 2011)
In the present study, a new natural and environmentally friendly drag reducing agent is introduced as a flow improver in pipelines carrying liquids in turbulent flow mode. The new drag reducing agent is extracted from the Aloe Vera leaves. The extracted mucilage drag reduction performance was tested using a closed loop liquid circulation system. The experimental work was carried out in 0.0254 m I.D. pipe with 100 to 400 ppm addition concentrations, four testing sections lengths and five different flow rates. It was found that the Aloe Vera mucilage was an effective drag reducing agent. A maximum drag reduction percentage of 63% could be achieved by adding 400 ppm of mucilage to the main flow. Drag reduction was found to increase with increasing Reynolds Numbers, additive concentrations and pipe lengths. Finally, a new correlation equation representing the experimental data is introduced.